2016
DOI: 10.1111/codi.13393
|View full text |Cite
|
Sign up to set email alerts
|

Once daily vs multiple daily mesalamine therapy for mild to moderate ulcerative colitis: a meta‐analysis

Abstract: OD dose of mesalamine is as effective and safe as MD doses for the induction and maintenance treatment of mild to moderate UC. OD mesalamine given as a suppository can attain the same effect and safety as MD mesalamine in inducing remission of mild to moderate ulcerative colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…A similar study with once daily and three times daily dosing of mesalazine also showed no difference in incidence of adverse events . Several other studies have similarly demonstrated no difference in adverse events between once daily compared to divided dosing for mesalazine …”
Section: Resultsmentioning
confidence: 71%
“…A similar study with once daily and three times daily dosing of mesalazine also showed no difference in incidence of adverse events . Several other studies have similarly demonstrated no difference in adverse events between once daily compared to divided dosing for mesalazine …”
Section: Resultsmentioning
confidence: 71%
“…The authors concluded that once-daily MSZ was effective in maintaining remission of UC for six months. Other authors have also observed that once-daily dose of mesalamine is as effective and safe as multiple daily doses for the induction and maintenance treatment of mild to moderate UC (8,9,19). Taking into account that once-daily dosing with 5-ASA is as effective as multiple doses it would be advisable to instruct patients to take a single daily dose to ease the treatment better than several administrations per day.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a meta-analysis evaluated the efficacy, safety and adherence to once-daily and multiple-daily dosing of mesalamine for the induction and the maintenance of remission in mild-to-moderate UC. 40 With respect to adherence, no difference was noted between the two doses of 5-ASA.…”
Section: Introductionmentioning
confidence: 92%